2014
DOI: 10.1371/journal.pone.0091454
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraoperative High-Dose Remifentanil on Postoperative Pain: A Prospective, Double Blind, Randomized Clinical Trial

Abstract: BackgroundRemifentanil, an ultra-short-acting opioid, is widely used for pain control during surgery. However, regular dose (RD) remifentanil exacerbates postoperative pain in a dose-dependent manner. Recent studies suggest that high-dose (HD) remifentanil offers sustained analgesia in experimental studies. We thus hypothesized that intraoperative administration of high-dose remifentanil may attenuate postoperative pain.MethodsIn this prospective, randomized, double blind, controlled clinical study, sixty pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…It has been demonstrated that intraoperative RI use may lead to acute opioid tolerance and a hyperalgesic state with increased postoperative pain and analgesic requirements. 6,8,9 We did observe that thyroidectomy patients who received RI intraoperatively also Abbreviations: CI, confidence interval; MMEs, morphine milligram equivalents. Intraoperative narcotics and maximum postoperative pain mean differences were adjusted for age, gender, BMI, ASA, surgical approach, amount of intraoperative acetaminophen, amount of anesthesiologist administered lidocaine, and OR (odds ratio) time.…”
Section: Discussionmentioning
confidence: 75%
“…It has been demonstrated that intraoperative RI use may lead to acute opioid tolerance and a hyperalgesic state with increased postoperative pain and analgesic requirements. 6,8,9 We did observe that thyroidectomy patients who received RI intraoperatively also Abbreviations: CI, confidence interval; MMEs, morphine milligram equivalents. Intraoperative narcotics and maximum postoperative pain mean differences were adjusted for age, gender, BMI, ASA, surgical approach, amount of intraoperative acetaminophen, amount of anesthesiologist administered lidocaine, and OR (odds ratio) time.…”
Section: Discussionmentioning
confidence: 75%
“…35 All trials administered opioids before surgical incision. The administered dose ratio between lowand high-dose groups were respectively 1:15 in one trial, 27 between 1:8 and 1:6 in five trials, 29,34,37,41,52 between 1:5 and 1:2 in 18 trials 26,28,[31][32][33]35,36,[38][39][40]42,43,[46][47][48][49][50][51] and at a ratio of 1:1.5 in three trials. 30,44,45 Of note, one trial administered dose that are beyond what is commonly used in the clinical practice.…”
Section: Re Sultsmentioning
confidence: 99%
“…Over 60% (18 of 27) of the included trials used a volatile-based anaesthesia maintenance, [26][27][28][29][33][34][35][37][38][39][40][41][42]44,46,48,50 while the remaining trials administered propofol. [30][31][32]36,43,45,47,49,51,52 Regarding the types of surgery, authors included patients scheduled for gynaecological surgery in seven trials, [27][28][29][30]35,42,44 for abdominal surgery in nine trials, 33,34,[37][38][39]41,43,49,50 for cardiac surgery in four trials, 31,32,45,51 and finally, we combined the remaining seven trials together into an "other surgeries" group. 26,…”
Section: Re Sultsmentioning
confidence: 99%
See 2 more Smart Citations